The challenges of conjunctively written adjectives in the learning of Sesotho - Makoa, Malisema Francina (Edelweiss Applied Science and Technology, 2024)
The use of adjectives in a sentence is a critical issue in various settings, especially when learning grammar, and is essential for comprehending the qualities that are associated with nouns. Adjectives are the words that add more information to the substantive (noun and pronoun) or the words that qualify the substantive, and they are one type of qualificative. Different languages have different orthographies of the adjectives. Some scholars have already shown the importance of adjectives in a sentence; however, some studies have indicated that some students have some challenges in writing the adjective in a sentence. Therefore, this study aims to find the challenges that conjunctively written Sesotho adjectives bring in the learning of Sesotho and how students can be assisted in writing the adjectives correctly. This interpretive study employed a qualitative approach where documents were used to gather data, and the data collected were analyzed thematically. The study found that students write the adjectives conjunctively instead of writing them disjunctively, which happened to be the problem under study. It concludes that students write adjectives conjunctively because they cannot separate the adjectival prefix from the adjectival stem. Therefore, the paper recommends that students be taught the structure of the Sesotho adjective as a separate entity in the text.